Efficacy of Availa®Cr (chromium chelate of dl‐methionine) as a feed additive for dairy cows (Zinpro Animal Nutrition (Europe), Inc) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal, 2023)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the efficacy of Availa®Cr (active compound: chromium chelate of dl‐methionine) as a feed additive for dairy cows. In a previous opinion, the FEEDAP Panel concluded that Availa®Cr at a maximum recommended use level of 0.5 mg Cr(III) (8 mg Cr from Availa®Cr/cow per day) was safe for dairy cows and the consumers. Additionally, the FEEDAP Panel considered that the additives posed a risk to the user by inhalation, it was not irritant to skin and eyes, and it should be considered a skin sensitiser. The Panel could not conclude on the efficacy of the additive at the proposed conditions of use. Since the new information provided in the current application is lacking sufficient evidence, the FEEDAP Panel is still not in the position to conclude on the efficacy of chromium dl‐methionine from Availa®Cr.